2022
DOI: 10.1186/s12935-022-02633-8
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MIR4435-2HG: a key molecule in progression of cancer and non-cancerous disorders

Abstract: MIR4435-2HG (LINC00978) is a long non-coding RNA (lncRNA) that acts as an oncogene in almost all cancers. This lncRNA participates in the molecular cascades involved in other disorders such as coronary artery diseases, osteonecrosis, osteoarthritis, osteoporosis, and periodontitis. MIR4435-2HG exerts its functions via the spectrum of different mechanisms, including inhibition of apoptosis, sponging microRNAs (miRNAs), promoting cell proliferation, increasing cell invasion and migration, and enhancing epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 87 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…In particular, MIR4435-2HG , which is a long non-coding RNA, is also known as LncRNA-AWPPH , LINC00978 , or MORRBID ( Ghasemian et al, 2022 ). Interestingly, MIR4435-2HG overexpression has previously been associated with hypomethylation in gliomas ( Zhong et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, MIR4435-2HG , which is a long non-coding RNA, is also known as LncRNA-AWPPH , LINC00978 , or MORRBID ( Ghasemian et al, 2022 ). Interestingly, MIR4435-2HG overexpression has previously been associated with hypomethylation in gliomas ( Zhong et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used TCGA-HNSCC datasets and clinical samples to verify the high expression of MIAT in HNSCC tissues, but the high expression of MIAT was beneficial to the prognosis of patients, which may be a compensatory increase in tumor to increase the infiltration of tumor immune cells and improve the anti-tumor immunity of HNSCC patients. MIR4435-2HG has also been shown to be up-regulated in gastric cancer, hepatocellular cancer, colorectal cancer, ovarian carcinoma, and renal cell carcinoma, which can promote the expression of downstream target genes through sponging miRNAs, inhibit tumor cell apoptosis, and enhance cell proliferation, invasion, migration, and EMT [60]. Wang et al found that mir4435-2Hg was highly expressed in HNSCC tissues, and in vitro and in vivo experiments verified that MIR4435-2HG promoted HNSCC cell proliferation, migration, invasion, and tumor growth by regulating the miR-383-5P/RBM3 axis [61].…”
Section: Discussionmentioning
confidence: 99%
“…The self‐renewal capacity of cancerous cells was impaired after silencing SAMMSON, and its ability was recovered after SAMMSON overexpression 25 . EZH2 is a primary component of polycomb repressive complex 2 (PPRC2) 2 . CTNNBIP1 protein is a physiological negative regulator of the Wnt pathway that prevents interaction between CTNNB1 and TCF/LEF complex and inhibits Wnt signalling activation 33 .…”
Section: Sammson and Tumorigenesismentioning
confidence: 99%